EFISIENSI PASAR SAHAM SYARIAH DI INDONESIA BERDASARKAN PENGUMUMAN PERUBAHAN KOMPOSISI SAHAMDI JAKARTA ISLAMIC INDEX (JII) - Mas Nur Mukmin; Hermi Hermi (Jurnal Magister Akuntansi Trisakti, 2015)
This research is aim to figure out the information content and market efficiency of syariah stock exchange in Indonesia based on the announcement of the change of stock composition in Jakarta Islamic Index (JII). This research is addressed to the included and excluded stocks. This research use event study method. The window event last for seven days (t-3 to t+3).The result support signalling theory. There’s no abnormal return around the window event for the included stocks. Negative abnormal return exist for the excluded stocks. The result also showed that JII is an efficient market in a semi-strong form based on the announcement of the JII stock composition change.